PENGARUH TRANSACTION SPECIFIC CHARACTERISTICS TERHADAP CUSTOMER SATISFACTION DAN CUSTOMER LOYALTY PADA RESTORAN WINGHENG DI JAKARTA UTARA - Tunggalono, Hendra Kurniawan; Surjano, Irvan (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this study is to determine the effect of Special Transaction Characteristics on Customer Satisfaction and Customer Loyalty at Wingheng Restaurant in North Jakarta. The design of this research is to use descriptive, correlational, and causality research. In this study the data used are primary data and secondary data. The sampling technique used is non-probability sampling that is using purposive sampling method with a number of respondents of 259 selected respondents who have visited and ate or did take away or delivery at the Wingheng restaurant in North Jakarta, as decision makers or those who made payments, who regularly eats at Wingheng restaurant at least in the last 1 month, and has recommended the restaurant to others. The research method used is the Structural Equation Modeling (SEM) analysis method based on Partial Least Square (PLS). Transaction Specific Characteristics have an influence on Customer Satisfaction and Customer Loyalty. Customer Satisfaction has an influence on Customer Loyalty. Customer Satisfaction mediates the relationship between Transaction Specific Characteristics and Customer Loyalty.